Fulfilment Children's Rights in the Digital Age: Between Protection and Privacy - Ahmad Putra Syahpitri Rambe; Sammuel Putra; M. Saad Ramadhani; Chairul Bariah; Yati Sharfina Desiandri (Talenta Publisher, 2025)
The rapid development of digital technology has significantly transformed patterns of social interaction, particularly among children, who are increasingly active users of digital platforms such as YouTube, TikTok, and online gaming applications. While these platforms provide opportunities for creativity and educational development, they also expose children to substantial risks concerning privacy rights and personal data protection. This study aims to analyze the legal protection of children’s privacy rights in the digital era from the perspectives of human rights and constitutional law. The research employs a normative juridical method using statutory, conceptual, and comparative approaches by examining child data protection practices in several countries. The findings reveal that Indonesia’s legal framework, including Child Protection Law of Indonesia and Personal Data Protection Law of Indonesia, has not specifically regulated the protection of children’s personal data in a comprehensive manner. In addition, institutional coordination among KPAI, Kominfo, and Kemendikbudristek remains ineffective, resulting in suboptimal supervision of children’s digital activities and content exposure. Therefore, the study emphasizes the urgency of establishing implementing regulations specifically oriented toward child data protection, strengthening digital literacy programs, and developing child-friendly algorithmic monitoring systems. The protection of children’s rights in the digital environment constitutes not only a legal obligation of the state but also a constitutional and moral commitment to safeguarding human dignity in the technological era.